1976
DOI: 10.1111/j.1545-5300.1976.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Treatment Program for Psychogenic Pain

Abstract: The family characteristics associated with the presence of recurrent abdominal pain are identified. The involvement on the pediatrician and the effects of this involvement on the patient, family, and perpetuation of the symptoms are described. A successful therapeutic program combining behavior modification and family therapy is elaborated. Changes in the structure and functioning of the family are vital to the outcome of therapy and the prevention of recurrence of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…Minuchin [21] described in great detail the devel opment of anorexia nervosa and its relationship to intricate family dynam ics. Liebman et al [14] observed that families of chronic pain patients demonstrated a high level of enmeshment, rigidity, over-protectiveness, and poor problem-solving capability. They had little or no regard for the autonomy or privacy of each individual.…”
Section: Contribution Of Family Factors In the Etiology Of Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Minuchin [21] described in great detail the devel opment of anorexia nervosa and its relationship to intricate family dynam ics. Liebman et al [14] observed that families of chronic pain patients demonstrated a high level of enmeshment, rigidity, over-protectiveness, and poor problem-solving capability. They had little or no regard for the autonomy or privacy of each individual.…”
Section: Contribution Of Family Factors In the Etiology Of Chronic Painmentioning
confidence: 99%
“…Liebman et al [14] have extensively reported the application of struc tural family therapy in treating children with psychogenic pain and other conditions and their families. Khatami and Rush [11] reported treating 1 case with the structural family therapy approach.…”
Section: Family Treatment For Chronic Painmentioning
confidence: 99%
“…* Many other studies which have been published suffer from poor research design, and the claimed results require substantiation. For example, the Philadelphia team have reported outcome studies of family therapy for a variety of childhood problems (Minuchin, Baker, Rosman, Liebman, Milman and Todd, 1975 ;Liebman, Honig and Berger, 1976), but exclude details of the methodology, fail to define criteria for improvement, and have not used control groups. This is disappointing because the results claimed are spectacular.…”
Section: Resultsmentioning
confidence: 99%
“…La première intervention thérapeutique consista à fixer la tâche suivante : la fillette devait noter chaque jour sur une feuille les heures où elle avait mal à l'estomac et devait la montrer à son père (Liebman et al, 1976;White, 1979). Ce dernier devait décider quand elle devait ou ne devait pas aller à l'école.…”
Section: Phobie De L'écoleunclassified